RETRACTED: Innovations in environmental education: The role of Information technologies in sustainable development - Adieva Aina; Vagapov Aidar; Kafarova Kizkhanum (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001